Bone-kidney axis: A potential therapeutic target for diabetic nephropathy - Yang, Ming; Luo, Shilu; Yang, Jinfei; Chen, Wei; He, Liyu; Liu, Di; Zhao, Li; Wang, Xi (Frontiers in Endocrinology, 2022)
Diabetic nephropathy (DN) is the leading cause of end-stage renal disease (ESRD). However, its pathogenesis remains unclear, and effective prevention and treatment strategies are lacking. Recently, organ-to-organ communication has become a new focus of studies on pathogenesis. Various organs or tissues (the liver, muscle and adipose tissue) secrete a series of proteins or peptides to regulate the homeostasis of distal organs in an endocrine manner. Bone, an important part of the body, can also secrete bone-derived proteins or peptides that act on distal organs. As an organ with high metabolism, the kidney is responsible for signal and material exchange with other organs at any time through circulation. In this review, we briefly discussed bone composition and changes in bone structure and function in DN and summarized the current status of bone-derived proteins and their role in the progression of DN. We speculated that the “bone-kidney axis” is a potential target for early diagnosis and treatment of DN.